Information and consumer willingness to pay for biofortified yellow cassava: evidence from experimental auctions in Nigeria. (23rd February 2016) - Oparinde, Adewale; Banerji, Abhijit; Birol, Ekin; Ilona, Paul
Abstract: In this article, we use the Becker‐DeGroot‐Marschak mechanism to estimate consumer demand for biofortified yellow cassava varieties in two states of Nigeria: Imo in the southeast and Oyo in the southwest. These two states exhibit distinct habitual product color preferences for staple food made with cassava. We estimate the effect of nutrition information campaigns and nature of planting material delivery institutions on consumer demand. Willingness to pay estimations account for the effect of product endowment, censoring in bids and nonpayment. In Oyo, consumers are willing to pay a premium for light yellow cassava variety even in the absence of nutrition information. The article finds that nutrition information results in a large and significant price premium for biofortified cassava in both states, and the nature of delivery institution has no significant effect.